Back Cover: Preparation of a Sulfo‐Group‐Containing Rod‐Like Polysilsesquioxane with a Hexagonally Stacked Structure and Its Proton Conductivity (Chem. Eur. J. 30/2014). Issue 30 (21st July 2014) - Kaneko, Yoshiro; Toyodome, Hisaya; Mizumo, Tomonobu; Shikinaka, Kazuhiro; Iyi, Nobuo
<x xml:space="preserve">Abstract</x> A sulfo‐group‐containing rod‐ and ladder‐like polysilsesquioxane with a hexagonally stacked structure (PSQ‐SO3H) was successfully prepared by oxidation and hydrolytic polycondensation of 3‐mercaptopropyltrimethoxysilane (MPTMS) in a mixed aqueous solution of NaOH and H2O2. The proton conductivity of the PSQ‐SO3H film determined using complex impedance spectroscopy was relatively high (>10−2 S cm−1) at 80 °C and 30–90% relative humidity. In the PSQ‐SO3H film, the protons likely migrate through the spaces between the regularly arrayed rod‐ and ladderlike polymers. For more details see the Full Paper by Y. Kaneko et al. on page 9394.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>